Bacterial Uropathogens and their Antibiotic Sensitivity Pattern at a Tertiary Care Hospital in Birgunj, Nepal - Bhargava, Dipak; Pandit, Bijay Raj; Shidiki, Amarullah; Gupta, Ravi Shankar (Med Phoenix, 2017)
Urinary tract infection is the second most common infection following respiratory tract infection. Among the outdoor and the indoor patients it is one of the common clinical state of affairs. For the effective management of this common clinical condition isolation of the common bacterial uropathogens and their antibiotic sensitivity profile is obligatory. In this present brief work an effort has been made to isolate the common bacterial uropathogen and their susceptibility pattern to the regularly used antimicrobial agents. We carried out this work in the Microbiology department of National Medical College from June 2016 to December 2016. In our study beside clean catched mid stream urine sample, catheterized urine sample and suprapubic aspirates are also collected. In our study we included a total of 516 UTI samples of patients. In our work 319 (62%) culture positive urine samples were from outpatient patient department while 197 (38%) were from inpatient department. Among both the outdoor and the indoor patient E. coli was the predominant organism followed by Klebsiella, Staphylococci, Enterococci and Pseudomonas. In our present work we found that the common bacterial isolates from the indoor patient showed higher degree resistance towards Aminopenicillin, Piperacillin, Nitrofurantoin, Ciprofloxacin and Nalidixic acid. Common bacterial uropathogens were found to be sensitive against Norfloxacin, Nitrofurantoin and Cephalosporins like Cefuroxime and Ceftazidime. It has also been found that beside E. coli other bacterial uropathogens were effective against third generation Cepahalosporins and Amikacin. This study clearly denotes that antibiotic sensitivity test should be carried out for determination of optimal treatment regimen against UTI. Med Phoenix Vol.2(1) July 2017, 74-77